BS EN 61753-021-02 Ed.3.0. Fibre optic interconnecting devices and passive components performance standard. Part 021-02. Grade C/2 single-mode fibre optic connectors for category C. Controlled environment (22nd December 2020) - British Standards Institution,
No abstract available